Mapping Potential Agriculture Sectors In The SULAMPUA Region As An Impact of Capital City of Nusantara Development - Ernawati, Ernawati; Nur, Syamsir; Asri, Mansyur (Journal of Business Management and Economic Development, 2024)
The development of Capital City of Nusantara (IKN), which is geographically closer to the SULAMPUA region, expected trigger the SULAMPUA economy, especially the agricultural sector. This study aims to determine the potential agricultural sector in the SULAMPUA region due to IKN development. The study uses IRIO (Inter-Regional Input-Output) from Statistics Indonesia in 2021, specifically for seven agricultural sub-sectors. The SULAMPUA region comprises ten provinces, with the Golden Triangle region comprising South Sulawesi, Central Sulawesi, and West Sulawesi. The results of the study show that no agricultural industry is a strategic sector in the SULAMPUA. Based on the criteria set out in the research, no sector falls into the category of very potential to be developed. The potential sectors to be developed in the SULAMPUA Region are (1) food crops; (2) seasonal and annual plantation crops; (3) livestock; (4) forestry and logging; and (5) fishery. Local governments need to consider policies related to potential agricultural sectors. Because the agricultural sector is a labor-intensive and the availability of resources.